Evaluation of predicted patellofemoral joint kinematics with a moving-axis joint model. (November 2019) - Dzialo, C.M.; Pedersen, P.H.; Jensen, K.K.; de Zee, M.; Andersen, M.S.
Highlights: Subject-specific moving-axis model better predicts patellar motion than hinge joint. Computational efficiency of model allows for potential use in clinical applications. Patellofemoral moving-axis model not suitable for those with patella instability. Abstract: The main objectives of this study were to expand the moving-axis joint model concept to the patellofemoral joint and evaluate the patellar motion against experimental patellofemoral kinematics. The experimental data was obtained through 2D-to-3D bone reconstruction of EOS images and segmented MRI data utilizing an iterative closest point optimization technique. Six knee model variations were developed using the AnyBody Modeling System and subject-specific bone geometries. These models consisted of various combinations of tibiofemoral (hinge, moving-axis, and interpolated) and patellofemoral (hinge and moving-axis) joint types. The newly introduced interpolated tibiofemoral joint is calibrated from the five EOS quasi-static lunge positions. The patellofemoral axis of the hinge model was defined by performing surface fits to the patellofemoral contact area; and the moving-axis model was defined based upon the position of the patellofemoral joint at 0° and 90° tibiofemoral-flexion. In between these angles, the patellofemoral axis moved linearly as a function of tibiofemoral-flexion, while outside these angles, the axis remained fixed. When using a moving-axis tibiofemoral joint, a hinge patellofemoral joint offers (−5.12 ± 1.23 mm, 5.81 ± 0.97 mm, 14.98 ± 2.30°, −4.35 ± 1.95°) mean differences (compared to EOS) while a moving-axis patellofemoral model provides (−2.69 ± 1.04 mm, 1.13 ± 0.80 mm, 12.63 ± 2.03°, 1.74 ± 1.46°) in terms of lateral-shift, superior translation, patellofemoral-flexion, and patellar-rotation, respectively. Furthermore, the model predictive capabilities increased as a direct result of adding more calibrated positions to the tibiofemoral model (hinge-1, moving-axis-2, and interpolated-5). Overall, a novel subject-specific moving-axis patellofemoral model has been established; that produces realistic patellar motion and is computationally fast enough for clinical applications.